2016
DOI: 10.1016/j.phrs.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMPK inhibits PDGF-induced pulmonary arterial smooth muscle cells proliferation and its potential mechanisms

Abstract: The aims of the present study were to examine signaling mechanisms for PDGF-induced pulmonary arterial smooth muscle cells (PASMC) proliferation and to determine the effect of AMPK activation on PDGF-induced PASMC proliferation and its underlying mechanisms. PDGF activated PI3K/Akt/mTOR signaling pathway, and this in turn up-regulated Skp2 and consequently reduced p27 leading to PASMC proliferation. Prior incubation of PASMC with metformin induced a dramatic AMPK activation and significantly blocked PDGF-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 40 publications
6
28
0
Order By: Relevance
“…Metformin is an in vitro synthetic AMPK agonist which has been commonly used in clinic to treat type 2 diabetes with wide clinical experience and safety record [ 49 ]. We have recently found that activation of AMPKα2 by metformin suppresses PASMCs proliferation [ 50 ], together with our current findings, suggesting that metformin might be used in clinical treatment of PAH. Yet, this still needs to be tested in patients with PAH.…”
Section: Discussionsupporting
confidence: 86%
“…Metformin is an in vitro synthetic AMPK agonist which has been commonly used in clinic to treat type 2 diabetes with wide clinical experience and safety record [ 49 ]. We have recently found that activation of AMPKα2 by metformin suppresses PASMCs proliferation [ 50 ], together with our current findings, suggesting that metformin might be used in clinical treatment of PAH. Yet, this still needs to be tested in patients with PAH.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have shown that AMPK promotes SMC proliferation and the development of pulmonary hypertension, which was reversed with AMPK inhibition (Ibe et al, 2013;Moral-Sanz et al, 2016). Conversely, other studies have shown that AMPK activation reduced SMC proliferation and vascular remodeling and may be protective against the development of hypoxia-induced pulmonary hypertension (Agard et al, 2009;Dean et al, 2016;Song et al, 2016). Importantly, in our present study, hPASMC proliferation was decreased with AMPK activation by AICAR ( Figure 6).…”
Section: F I G U R Esupporting
confidence: 53%
“…Whereas NO acts as both a target and an effector of the AMPK pathway in endothelial cells (Fisslthaler & Fleming, 2009;Suzuki et al, 2008), less is known about the mechanism by which NO regulates AMPK in smooth muscle cells. Moreover, data on the role of AMPK in vascular proliferation and pulmonary hypertension are conflicting (Agard et al, 2009;Dean, Nilsen, Loughlin, Salt, & MacLean, 2016;Ibe et al, 2013;Moral-Sanz et al, 2016;Salt & Hardie, 2017;Song et al, 2016). Several studies have shown that AMPK promotes SMC proliferation and the development of pulmonary hypertension, which was reversed with AMPK inhibition (Ibe et al, 2013;Moral-Sanz et al, 2016).…”
Section: F I G U R Ementioning
confidence: 99%
“…Our ssGSEA/GSEA analysis showed that the "metformin_downregulated" signature and NFkB signaling exhibited a good consistency with the activated stromal fibroblast phenotype corresponding to the acknowledged pathway characteristically activated in CAFs (46) such as TGFb, IGF1/PI3K/mTOR, PDGF, and the JAK/STAT signaling. Actually, all these signaling factors associated with CAFs activation have been reported to be inhibited by metformin in fibroblasts or other cells (23,45,54,60,61). These preliminary results indicate that metformin will likely exert a multiple reprogramming of CAFs in ovarian cancer.…”
Section: Discussionmentioning
confidence: 71%